Medical Imaging 2019: Image-Guided Procedures, Robotic Interventions, and Modeling 2019
DOI: 10.1117/12.2513613
|View full text |Cite
|
Sign up to set email alerts
|

Automatic segmentation of brain tumor resections in intraoperative ultrasound images

Abstract: The brain is significantly deformed during neurosurgery, in particular because of the removal of tumor tissue. Because of this deformation, intraoperative data is needed for accurate navigation in image-guided surgery. During the surgery, it is easier to acquire ultrasound images than Magnetic Resonance (MR) images. However, ultrasound images are difficult to interpret. Several methods have been developed to register preoperative MR and intraoperative ultrasound images, to allow accurate navigation during neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…We first tested a 2-D version which was applied to iUS images to segment the resection cavity in brain tumor surgeries in another study. 12 We trained two networks 2D-1 and 2D-9 with one and nine adjacent slices as input, respectively. Input size was 256x256, so we used a sliding window (with a stride of 64) for the training and testing phases.…”
Section: Segmentation Networkmentioning
confidence: 99%
“…We first tested a 2-D version which was applied to iUS images to segment the resection cavity in brain tumor surgeries in another study. 12 We trained two networks 2D-1 and 2D-9 with one and nine adjacent slices as input, respectively. Input size was 256x256, so we used a sliding window (with a stride of 64) for the training and testing phases.…”
Section: Segmentation Networkmentioning
confidence: 99%
“…We expect the proposed registration approach to achieve better results than the same method not excluding the resection cavity. Regarding the segmentation step, to the best of our knowledge only the authors in [20,21] proposed a solution for this task. In [21], they described a method based on a 2D U-Net to segment the resection cavity in US volumes.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the segmentation step, to the best of our knowledge only the authors in [20,21] proposed a solution for this task. In [21], they described a method based on a 2D U-Net to segment the resection cavity in US volumes. Besides, in [20] they also demonstrated that the 3D architecture achieves better results than a 2D approach.…”
Section: Introductionmentioning
confidence: 99%